Toward automating affordance-based design. Issue 3 (28th July 2015) - Brown, David C.; Maier, Jonathan R.A.; Mata, Ivan; Fadel, Georges; Mocko, Gregory
Abstract The objective of this research is to develop a computational representation of knowledge associated with affordance-based design (ABD). The ABD ontology formalizes the entities, properties, and relationships within the domains of ABD. The ontology enables designers to describe the affordances of existing products and specify the intended affordances of future products in line with ABD. The ontology consists of 14 concepts and 5 relationships. The ontology is developed using Protégé 4.3 and DL-query to query and reason with the ontology. The ontology is demonstrated using a consumer vacuum cleaner. The formal ontology serves as the basis for developing computer support for ABD applications. When implemented, these design tools will help designers manage the affordances of artifacts being designed, specifying the interacting entities of every affordance when a three-dimensional model of the artifact is available. Further, these software tools could be used to support ABD methods.